SENSE-CREATIVE CONTEXT AS A FACTOR OF LEARNER AUTONOMY IN A FOREIGN LANGUAGE ACQUISITION - Stakanova, Elena (PEOPLE: International Journal of Social Sciences, 2017)
The current study reveals the concept of sense-creative context as a factor of autonomy in learning a foreign language. Sense-creative context is a system of sense technologies that motivates students who are eager to know how to improve their knowledge. Using sense-creative technologies in teaching EFL is becoming a burning issue in the modern classroom due to the challenges University graduates face in real life. Sense-creative context in our study has been analyzed and implemented in EFL teaching with a focus on personal and meaningful development of the students. Three groups of students were formed (control group and two experimental groups). All were native speakers of Russian who studied English at Psychology Department of Southern Federal University, Rostov-on-Don, Russia. The control group mastered English fluently; some of them had passed Cambridge Examinations FCE, CAE. The second experimental group was taught English using regular and typical classroom activities. We administered sense-creative technologies, such as PLE, debates, projects to the third experimental group to form deep personal meaning and intrinsic motivation. The objective of the research was to find out that with the help of sense-creative strategies in learning a foreign language it is possible to observe the students’ vocational aspirations, self-assessment and learner autonomy. The results have pedagogical implications for EFL curriculum and all who are involved in the language study. To recap, using the sense-creative context, we change the priorities and form sense-creative approach, the essence of which is to put students in the conditions when he/she feels the intrinsic need to acquire knowledge.